Hyperexpression of TLR2 and TLR4 in patients with ischemic stroke in acute period of the disease - L. V. Gankovskaya (SPb RAACI, 2020)
Pathogenesis of ischemic stroke  is actively  involved  in the  system  of innate immunity. Under conditions of cerebral  ischemia, a number of biologically  active  substances are  released  that  interact with innate immunity receptors, in particular TLR2  and  TLR4, which  exacerbate inflammation in brain  tissue. Identification of predictor markers  at the level of the innate immunity system may foresee the clinical course of ischemic stroke and ensure timely treatment. Our objective was to study expression of TLR2 and TLR4 receptors in peripheral blood leukocytes  in patients with ischemic stroke in the dynamics of the disease. 27 people  were included in the study. The main  group consisted of patients with ischemic stroke of varying severity (n = 19). Patients of the main  group were divided into two subgroups:  with an NIHSS index value of < 10 (n = 10) and > 10 (n = 9). The control group included healthy  donors  with no history  of acute  and chronic inflammatory diseases (n = 8). Peripheral blood  leukocytes  were used as the  test material. To determine expression  of the TLR2  and TLR4  genes, RT-PCR in real time was used. Surface  expression  of TLRs was determined by flow cytometry. A study of the TLR2 and TLR4 gene expression showed that on the 1st, 3rd  and 7th  day post-stroke, the TLR4 gene expression  in patients was significantly  increased, when compared to the control group (p < 0.01), whereas TLR2 gene expression on the 3rd  day of the disease was not statistically different from the control group. A study of surface expression  of receptors showed that the average TLR2 fluorescence intensity on the patients’ peripheral blood monocytes was significantly  increased on the 1st  and 3rd  day of disease when compared to the control group.  The  surface  expression  of TLR4  on monocytes has a statistically significant  increase  only on day 7. Assessment  of surface expression  of TLRs in subgroups  with different  severity values by NIHSS showed that  patients with a NIHSS index > 10 had a significantly  higher  level of surface of TLR2  expression  over the observation period, while the largest difference in TLR4  expression  in the subgroups  was observed  on the 1st day of the disease (p < 0.05). Patients with ischemic stroke showed an increase  in TLR2 and TLR4 expression at the gene and protein level, compared to healthy  donors. These indices can be considered possible predictors for clinical  prognosis  of ischemic stroke.